IbM Koperasi “Rukun Agawe Santoso” Pasar Kranggan Yogyakarta dan Koperasi “Maju Lancar” Pasar Cokrokembang Klaten - Dyna Herlina Suwarto; Bambang Suprayitno; Purwo Adi Wibowo (Universitas Islam Nahdlatul Ulama Jepara, 2018)
In general, the Kranggan market cooperative in Yogyakarta and the Cokrokembang Market Cooperative in Klaten are faced with the following problems: l) The weak aspects of cooperative administration, administration of recording and finance are still very simple (manual); 2) The weakness of organizational aspect, there are no clear rules and no standard operational standard, 3) Management aspect, lack of management skill in saving and loan environment. Goals and Outcomes include: 1) software and financial systems to manage, and efficiency; 2) establishment of AD / ART; 3) compilation of SOP manual. Method approach to overcome problems with training, preparation of accounting systems and finance cooperatives, and mentoring. The training plan consists of 1) administrative and bookkeeping training of saving and loan cooperatives, 2) institutional & cooperative management training, 3) training and practice of the financial system and finance of the cooperative. The preparation of the cooperative financial and accounting system is carried out by the implementing team of IbM. The plan of assistance activities undertaken is the assistance of the preparation of AD/ART, Standard Operating Procedures (SOP) and working procedures of cooperative institutions.